Muhammadiyah Paradigma Gerakan Sosial Keagamaan - Saguni, Muhammad Kasim (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2018)
Muhammadiyah is one of the Islamic mass organizations establish in the 1912s and has operated in many aspects of life including religion, social, education, healthcare, and politic. In addition, Muhammadiyah has big impacts on determining the decisions and policies of the Indonesian elites. This journal analyzes history of the establishment and the development of Muhammmadiyah specifcally on the eï¬€orts conducted by Muhammadiyah, adopted religious paradigm, prominent figures reactions to Muhammadiyah